Practice tests for IELTS - Travis, Peter; Harrison, L. (Louis) (Collins English for exams, 2013)
All you need for your ideal IELTS score: - Four complete Academic IELTS tests - PLUS Two complete General Reading and Writing papers - A clear guide to how the IELTS exam works - A whole section full of useful tips on how to do well in the exam - A CD (+ transcript) with accurate model Speaking and Listening papers - Answers and explanations for all four papers (including model answers for Speaking and Writing)